Systematic phonics intervention and its impact on the development of phonics skills and speech perception among children with hearing loss using spoken language - Abdul Rahim, Zurahani; Brown, P. Margaret (International Academic Research Journal, 2015)

(untitled)
Literacy studies on children with hearing loss suggest possible benefits of systematic phonics instruction focusing on automatic recall of visual patterns and auditory-visual memory of sounds /letters. Few studies have looked at the impact of phonics in developing various speech-language skills among children with hearing loss who use spoken language. It was hypothesized that intensive phonics intervention would lead to better phonics skills among participants and that such phonics training would lead to better speech perception levels. The findings of the study indicated positive results in the development of practical phonics skills based on the THRASS© programme. However, a mixed result was evident for speech perception following the implementation of ten weeks of intervention. Poor long-term retention of the acquired skills at post-intervention suggests a need for a prolonged period of intervention to show any significant change. The heterogeneity of hearing levels among participants and the stringency of methods for speech perception analysis may have also contributed to the differing results across speech perception measures. Data suggests that improvements varied across the whole range of micro skills with overall speech perception and vowel perception skills lagging behind word and consonant perception skills despite improvements in phonics skills.